Exploring Emoji Functions in Comments on Game Trailers with Different Target Audiences - Christopher Yeung (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study explores the emoji functions in Instagram comments on two game trailers targeting different age groups using Yus’ (2014) eight-function taxonomy. This study analyzes Instagram comments on two game trailers that are aimed at different age groups, not comments written by confirmed adults or children. A qualitative approach was employed, with data containing 70 Elden Ring and 79 Toca Boca World comments. Key findings show that the Elden Ring comments used all eight emoji functions while the Toca Boca World comments used only six of them The study also found single emojis performing two roles simultaneously and decorative emojis that do not fit into Yus’ (2014) taxonomy. This research shows how commenters use emojis differently (or similarly) when reacting to content for distinct age groups. Future studies could analyse emoji functions on other online platforms, compare more game trailers, or examine differences across gender or cultural background.